Impact of the Iranian Health Sector Evolution Plan on Rehospitalization: An Analysis of 158000 Hospitalizations - Ali JANATI; Reza EBRAHIMOGHLI; Homayoun SADEGHI-BAZARGANI; Masoumeh GHOLIZADEH; Firooz TOOFAN; Hojatolah GHARAEE (Tehran University of Medical Sciences, 2020)
Background: In May 2014, Iran launched the most far-reaching reform for the health sector, so-called Health Sector Evolution Plan (HSEP), since introduction of the primary health care network, with a systematic plan to bring about Universal Health Coverage. We aimed to analyze the time to first all-caused rehospitalization and all-caused 30-day readmission rate in the biggest referral hospital of Northwest of Iran before and after the reform. Methods: We retrospectively analyzed discharge data for all hospitalization occurred in the six-year period of 2011-2017. The primary endpoints were readmission-free survival, and overall 30-day readmission rate. Using multivariate cox proportional hazards regression and logistic regression, we assessed between-period differences for readmission-free survival time and overall 30-day rehospitalization, respectively.         Results: Overall, 157969 admissions were included. After adjusting for available confounders including age; sex; ward of admission; length of stay; and admission in first/second half of year, the risk of being readmitted within 30 days after the reform was significantly higher (worse) compared to pre-reform hospitalization (odd ratio 1.22, P<0.001, 95% CI, 1.15-1.30 ). Adjusting for the same covariates, after-reform period also was slightly significantly associated with decreased (deteriorated) readmission-free time compared with pre-HSEP period (HR 1.06, P=0.005, 95% CI 1.01-1.11). Conclusion:  HSEP seems insufficient to improve neither readmission rate, nor readmission-free time. It is advisable some complementary strategies to be incorporated in the HSEP, such as continuity of care promotion, self-care enhancement, effective information flow, and post-discharge follow up programs.